Metabotropic glutamate receptor 5 as a potential therapeutic target in Huntington's disease. (1st November 2014) - Ribeiro, Fabiola M; Hamilton, Alison; Doria, Juliana G; Guimaraes, Isabella M; Cregan, Sean P; Ferguson, Stephen SG
Abstract : Introduction: Huntington's disease (HD) is an autosomal dominant neurodegenerative disorder caused by a polyglutamine expansion in the amino-terminal region of the huntingtin (htt) protein, which underlies the loss of striatal and cortical neurons. Glutamate has been implicated in a number of neurodegenerative diseases, and several studies suggest that the metabotropic glutamate receptor 5 (mGluR5) may represent a target for the treatment of HD. Areas covered: The main goal of this review is to discuss the current data in the literature regarding the role of mGluR5 in HD and evaluate the potential of mGluR5 as a therapeutic target for the treatment of HD. mGluR5 is highly expressed in the brain regions affected in HD and is involved in movement control. Moreover, mGluR5 interacts with htt and mutated htt profoundly affects mGluR5 signaling. However, mGluR5 stimulation can activate both neuroprotective and neurotoxic signaling pathways, depending on the context of activation. Expert opinion: Although the data published so far strongly indicate that mGluR5 plays a major role in HD-associated neurodegeneration, htt aggregation and motor symptoms, it is not clear whether mGluR5 stimulation can diminish or intensify neuronal cell loss and HD progression. Thus, future experiments will be necessary to further investigate the outcome of drugs acting on mGluR5 for the treatment of neurodegenerative diseases.